Report of the Monopolies and Mergers Commission : second response by the Authority (Civil Aviation Authority LondonGB, 1985)
Records the progress made by the Civil Aviation Authority since February 1984 in implementing new policies and procedures some of which respond directly to remedies proposed by the Monopolies and Mergers Commission (MMC) whilst others were already in train before the MMC investigation was conducted.
DC